2020
DOI: 10.1186/s12986-020-00441-3
|View full text |Cite
|
Sign up to set email alerts
|

Anorexic and metabolic effect of jojoba: potential treatment against metabolic syndrome and hepatic complications

Abstract: Background: Evaluation of the action of various traditional plants to treat metabolic syndrome are strongly studied. In our study, we investigated the effect of the Tunisian jojoba seed on a metabolic syndrome induced in rat by the High Fat diet and High Fructose (HFHF) and its renal and hepatic complications. Methods: The rats were fed with HFHF or Normal Diet (ND) for a period of 8 weeks. After that, a switch from HFHF to ND or Normal Diet Jojoba (NDJ),(jojoba diet approach) or High Fat and High Fructose and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…The improved FCR can result in increased growth performance and meat quality of broilers raised under hot climatic condition. Jojoba oil has antimicrobial and antioxidant activities [18,26] that may support improvements in broiler performance in this study. Supplementation of Hippophae rhamnoides extract as a phytogenic feed additive in broiler diets increased growth performance in chickens, leading to a subsequent improved economic return [12].…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…The improved FCR can result in increased growth performance and meat quality of broilers raised under hot climatic condition. Jojoba oil has antimicrobial and antioxidant activities [18,26] that may support improvements in broiler performance in this study. Supplementation of Hippophae rhamnoides extract as a phytogenic feed additive in broiler diets increased growth performance in chickens, leading to a subsequent improved economic return [12].…”
Section: Discussionmentioning
confidence: 66%
“…Concerning the carcass criteria in the current study, jojoba seed oil improved dressing percentage and decreased abdominal fat percentage at 35 days of age, which could be due to the biologically active chemical components of jojoba seed oil (Table 2). The decrease in abdominal fat is mainly due to PLBC in broilers' diet improving activities of amylase and trypsin [31,32] and secretion of bile acids [18,26,33,34]. Unfortunately, no literature is available on the effect of jojoba seed oil on the carcass criteria of broilers; therefore, the comparisons were performed with other phytogenics.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were confirmed in a recent study that indicated jojoba seeds induced a decrease in body weight, fat mass, insulin resistance, oxidative stress, liver steatosis and renal complications. The results demonstrated the beneficial effect of jojoba against metabolic syndrome and oxidative stress [ 48 ].…”
Section: Biological Activitymentioning
confidence: 99%
“…The increase in triglycerides mainly occurs due to high-fructose diets, whereas obesity occurs due to high-fat diets. This combination diet was associated with an increase in plasma cholesterol levels, a decrease in HDL cholesterol, and a 2-fold increase in liver weight in rats (Table-5) [39][40][41][42][43][44][45]. A study has shown the accumulation of lipids in the myocardium, left ventricular hypertrophy, and morphological liver damage.…”
Section: Combination Of High-fat and High-carbohydrate Diet Modelsmentioning
confidence: 99%